International Cooperation—International Organizations - Karska, Elżbieta (International Law From A Central European Perspective, 2022)
This chapter is devoted to the international organization as the legal form of international cooperation. It begins with an historical analysis, in which the author refers to the examples of ancient Greece and the local forms of cooperation between city-states, which are considered the precursors of today’s international organizations. The author subsequently discusses the historical changes over the last two centuries that gave rise to contemporary international organizations. Examples cited include universal and regional organizations such as the United Nations, the Council of Europe, the European Union, and the North Atlantic Treaty Organization. The author uses these examples as the basis for examining the goals of international cooperation as well as the principles and axiology of international organizations. Particular attention is paid to the goals of the international community, such as ensuring international peace and security, building common collective security, developing the principles of a democratic state of law, and developing the protection of human rights. In the following part, the author considers the attributes of an international organization that determine effective international cooperation. These include the right to conclude international agreements, the right to send and receive diplomatic representatives, the right to bring international claims, and the obligation to bear international responsibility. Conclusions regarding the role of states in creating international organizations and equipping them with specific competences in the sphere of international relations are important in this respect. This is fundamentally a question about the scope of subjectivity and legal capacity to act in the sphere of international law. In the penultimate part, the author considers the role of the organs of an international organization in making cooperation more effective and introduces categories of organs by dividing them according to various criteria. The paper ends with reflections on the changing needs of states and the international community that affect the goal of international cooperation and the legal form of its implementation, i.e., an international organization.KEYWORDS: international organization, international cooperation, United Nations, North Atlantic Treaty Organization, Council of Europe